Rich Grad, Poor Grad: Family Background and College Major Choice - Margaret Leighton; Jamin D. Speer (Institute of Labor Economics (IZA), 2023)
Expected earnings matter for college major choices, and majors differ in both their average earnings and the age profile of their earnings. We show that students' family background is strongly related to the earnings paths of the major they choose. Students with more educated parents, especially those who have graduate degrees, choose majors with lower early-career earnings but much faster earnings growth. They are also less likely to choose safe majors with little early-career earnings or unemployment downside. Parental income has a weaker relationship with major choice and operates mostly through the type of institution the student attends.
Keywords: I21; I23; 330; college major; family background